EVALUATE THE EFFECTIVENESS OF MICROFLUIDIC AND DENSITY GRADIENT SPERM PREPARATION METHODS ON POST-VITRIFICATION SPERM QUALITY (Vietnam Journal of Community Medicine, 2026)
Objective: Evaluate the effectiveness of microfluidic sperm preparation and density gradient centrifugation on post-vitrification sperm quality.Subject and methods: This study was conducted on semen samples meeting the criteria of the World Health Organization Laboratory Manual (2021). Each semen sample was divided into two aliquots and processed in parallel using microfluidic sperm preparation and density gradient centrifugation, followed by cryopreservation using the vitrification method. Sperm quality was evaluated after preparation, after thawing through the cryosurvival factor (CSF).Results: After sperm preparation, the microfluidic group showed significantly higher sperm concentration, viability, total motility, and progressive motility compared with the density gradient group. After vitrification, sperm quality decreased in both groups; however, the microfluidic group maintained higher values for these parameters than the density gradient group. The CSF values for sperm concentration, viability, and total motility did not differ significantly between the two methods, whereas the CSF for progressive motility was higher in the density gradient group.Conclusion: Microfluidic sperm preparation improves sperm quality after preparation and maintains better parameters after cryopreservation compared with density gradient centrifugation, suggesting its potential application in sperm selection prior to cryopreservation in assisted reproductive techniques.
Keywords: Sperm cryopreservation, microfluidics, density gradient centrifugation, vitrification.